Identification of mechanisms of natural resistance to African trypanosomiasis in cattle - Naessens, Jan; Teale, A.J.; Sileghem, M.R. (Elsevier, 2002)
Natural resistance to African trypanosomiasis in certain Bos taurus cattle in West Africa, called trypanotolerance, may hold solutions for control of this economically crippling disease. Comparison of immune responses between trypanotolerant and trypanosusceptible cattle have shown some differences in antibody response, complement level and cytokine expression, but it is not known whether these differences are the cause of resistance.